Pengaruh Aerasi Dalam Proses Biodrying Terhadap Karakteristik Lindi Pada Pengelolaan Sampah Organik - Nadira Prananda; Sri Sumiyati; Bimastyaji Surya Ramadan (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2026)
ABSTRAK Solid waste management, particularly organic waste, has become a major challenge due to the increasing waste generation and the growing demand for sustainable energy. One of the rapidly developing technologies for organic waste treatment is anaerobic digestion, which plays a crucial role in reducing waste volume while simultaneously recovering energy in the form of biogas. This study aims to analyze research trends, publication patterns, and the development of anaerobic digestion within the context of solid waste management using a bibliometric analysis approach. A Systematic Literature Review (SLR) was conducted based on the PRISMA guidelines, utilizing data retrieved from the Scopus database covering the period from 2015 to 2024. A total of 492 selected articles were analyzed using VOSviewer to identify annual publication trends, the most productive journals and authors, country contributions, keyword relationships, and major subject areas. The results indicate a significant increase in publications over the last decade, with Waste Management identified as the most relevant journal and China as the leading contributing country. The most frequently occurring keywords include anaerobic digestion, municipal solid waste, and waste management, reflecting the strong research focus on organic waste treatment and energy recovery. This study highlights the strategic role of anaerobic digestion as a sustainable technology in solid waste management systems and provides valuable insights to support future research development and policy implementation in waste management.